Bioinspired NiFe–gallate metal–organic frameworks for highly efficient oxygen evolution electrocatalysis. Issue 13 (15th March 2022) - Fang, Min; Gao, Xutao; Liang, Jing; Guo, Biao; Zou, Lie; Lu, Jun; Gao, Yan; Tse, Edmund C. M.; Liu, Jinxuan
Abstract : A bioinspired NiFe-gallate was synthesized on carbon paper. It exhibits superior OER performance with an overpotential of 185 mV at 10 mA cm –2 . Abstract : We report the synthesis of a bioinspired NiFe–gallate metal–organic framework on carbon paper using gallic acid (GA) as the organic ligand, nickel chloride hexahydrate and iron(ii ) chloride tetrahydrate as metal sources by a one-step hydrothermal method. The as-prepared NiFe–GA on carbon paper exhibits excellent oxygen evolution reaction (OER) performance, which requires overpotentials of 185 mV and 236 mV to achieve 10 mA cm −2 and 100 mA cm −2 in 1.0 M KOH, respectively. In situ electrochemical and density functional theory calculation results reveal that the presence of Fe and GA favors the generation of active oxygen species and the catalytic active Ni- and Fe-sites facilitate the charge transport to adsorbed OHad reducing the activation barrier of OHad deprotonation to form Oad intermediates, thereby contributing the superior OER performance.